Current Development on Origami/Kirigami‐Inspired Structure of Creased Patterns toward Robotics. Issue 10 (16th August 2021) - Ai, Chao; Chen, Yuting; Xu, Linghui; Li, Hong; Liu, Chen; Shang, Fangfang; Xia, Qingchao; Zhang, Sheng
Abstract : Origami/kirigami, the ancient art of paper folding and cutting techniques, has provided considerable inspiration for structural design routes in the engineering and medical fields over the last few decades. The practicability of the methods and concepts of origami/kirigami has been demonstrated in several emerging classes of technologies, e.g., stretchable electronics, deformable devices, self‐assembly fabrication, etc. More and more related products are produced pursuing a folding form for better storage, deformation capacity, and multifunction realization. Herein, the innovative creased patterns of origami/kirigami designs are distinguished and discussed, and the four most widely used creased pattern types are introduced, which may potentially provide origami/kirigami related inspiration and additional solutions toward many research fields. Abstract : Origami/kirigami techniques have provided considerable inspiration for structural design routes in the engineering and medical fields over the last few decades. Herein, the innovative creased patterns of origami/kirigami designs are distinguished and discussed, and the four most widely used creased pattern types are introduced, which may potentially provide origami/kirigami‐related inspiration and additional solutions toward many research fields.